Karakteristik dan Struktur Pendapatan Petani Singkong Kampung Adat Cireundeu - Suminartika, Eti; Ernah, Ernah; Amanda, Audi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Rasi is the main food of Kampung Adat Cirendeu people, old farmer age and low motivate of young generation in cassava farming become a serious problem in cassava farming, cassava is the raw material of rasi (the main food).  The purpose of this study is to analyse casava farmer-farm characteristic and to analyse the income structure of cassava farmer. The research use census method, the number of farmers is 12 farmers, the analyse of study  is statistic descriptive analyse. The result shows that the age of farmer is 65-year-old, the experience of farming is 40 years, the number of people in a family is 4 persons, the education of farmer is an elementary school.  The land area of farmer is 1,07 ha, the majority of them are land owner, farmer cultivate cassava by polyculture system. The majority (74%) of income came from non-agriculture sector, cassava farming and processing contribute 21%, another farming (non casava farming) contribute 1 % and livestock farm and farm worker contribute 4% of family income.  Therefore, the role of cassava farming and processing contribute less income to the family income.